Controlling the process of explosive destruction of rocks in order to minimize dust formation and improve quality of rock mass - Tverda, Oksana; Plyatsuk, Leonid; Repin, Mykola; Tkachuk, Kostiantyn (Eastern-European Journal of Enterprise Technologies, 2018)
Based on the adapted model by G.N. Lyakhov, we established a pattern in the propagation of pressure waves during explosive destruction of rocks, which relates to acoustic rigidity of the gap filler between the charge and the wall of the well and its size. It was determined that an increase in the acoustic rigidity of the solution proposed to be uses as a gap filler between the charge and the well reduces the peak of pressure in the zone close to the charge. In addition, the amplitude width of the pressure wave increases. An increase in the magnitude of the gap through the use of charges with smaller diameters enhances the effect of reducing the volume of dust formation. We have established regularities in the propagation of pressure waves related to acoustic rigidity of the gap filler between the charge and the borehole wall, as well as its magnitude, for different types of rocks. Specifically, for basalt, diabase, gabbro, granite, and limestone. It was determined that solutions with larger acoustic rigidity would reduce the amount of dust formation and improve the homogeneity of fractional composition of rock mass. That is possible by reducing the amplitude of pressure waves at the media interface and by increasing the width of the amplitude in any rock. In particular, filling the gap with the aqueous solution of iron (III) sulfate could reduce the amplitude of pressure waves by 20 %. The research results are important as they make it possible to control the process of explosive destruction of rocks. Such a control can be executed by changing the acoustic rigidity of the gap filler between the charge and the well, and by changing its size. Adjusting these parameters would not worsen the explosion results, such as, for example, reducing the consumption of an explosive or decreasing a diameter of the charge. On the contrary, it will ensure a more uniform distribution of pressure waves in rock, thereby reducing not only the environmental load, but the cost of finished products as well.